2018
DOI: 10.1097/brs.0000000000002648
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Patient Reported Outcomes Measurement Information System (PROMIS) Computer Adaptive Tests (CATs) in the Surgical Treatment of Lumbar Spinal Stenosis

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 28 publications
4
61
1
Order By: Relevance
“…14,[16][17][18][19] While the literature is still developing in assessing the concurrent validity of the PRO-MIS domains of Pain Intensity and Pain Interference in populations with thoracolumbar disorders, recent research by Papuga et al 4 similarly shows a strong correlation between PROMIS Physical Function and ODI score (R 2 ¼ 0.683) for patients presenting for spine surgical evaluation. In a population of patients undergoing surgical treatment for lumbar spinal stenosis, Patel et al 19 also showed multiple correlations between ODI and the PROMIS domains of Physical Function (r ¼ À0.58), Pain Intensity (r ¼ 0.73), and Pain Behavior (r ¼ 0.60), further demonstrating the convergent validity of PROMIS assessments. Our analysis adds to the growing body of literature describing the relationship between the "gold standard" legacy assessment of low back disability and the "new standard" of PROMIS.…”
Section: Discussionmentioning
confidence: 99%
“…14,[16][17][18][19] While the literature is still developing in assessing the concurrent validity of the PRO-MIS domains of Pain Intensity and Pain Interference in populations with thoracolumbar disorders, recent research by Papuga et al 4 similarly shows a strong correlation between PROMIS Physical Function and ODI score (R 2 ¼ 0.683) for patients presenting for spine surgical evaluation. In a population of patients undergoing surgical treatment for lumbar spinal stenosis, Patel et al 19 also showed multiple correlations between ODI and the PROMIS domains of Physical Function (r ¼ À0.58), Pain Intensity (r ¼ 0.73), and Pain Behavior (r ¼ 0.60), further demonstrating the convergent validity of PROMIS assessments. Our analysis adds to the growing body of literature describing the relationship between the "gold standard" legacy assessment of low back disability and the "new standard" of PROMIS.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in the spine literature have demonstrated that both are valid and responsive questionnaires. [14][15][16] The ODI and the NDI are 2 other commonly used questionnaires that have been in use since the early 1980s and are validated as useful clinical tools representing pain and disability. 17,18 The preoperative PROMIS scores were recorded, as well as the preoperative ODI and NDI scores.…”
Section: Methodsmentioning
confidence: 99%
“…Completion time tended to be shorter, and thus PROMIS measures could be more efficient than legacy measures. 46 It should be noted that if a comprehensive assessment of QOL is desired, numerous domains would need to be captured (e.g., physical, social, and emotional functioning, pain interference and pain behavior, positive affect, and well-being, etc. ), and thus the completion time would likely be similar to existing multidimensional outcome measures or combinations of such.…”
Section: The Promise Of Irtmentioning
confidence: 99%